Implementing the Cooperative Script Learning Model to Support Elementary Students’ Speaking Skills - Ismi Dzulqaidah; St Kuraedah; Karim (Jurnal Wawasan Sarjana, 2024)
This research aims to improve students' speaking skills through the implementation of the Cooperative Script learning model in Class IV of SDN 5 Wawolesea. This study uses classroom action research (CAR), which involves four stages: planning, implementation, observation, and reflection. The subjects of the research are 10 fourth-grade students from the 2023/2024 academic year. The study was conducted in two cycles, with each cycle consisting of two meetings. Before the implementation of the model, the students' speaking performance was low, with only 47.5% of students achieving the expected outcomes and an average score of 47.5. In Cycle I, teacher and student activities improved, and student speaking skills increased to 53% in the first meeting and 58.5% in the second meeting. However, this had not yet met the success indicator of 75%. Therefore, the study continued to Cycle II. In this cycle, teacher and student participation improved significantly. In the first meeting, students’ speaking skills rose to 64.5%, and in the second meeting, they reached 76%, with an average score of 76. Eight out of ten students were present. These results indicate that the Cooperative Script learning model can effectively enhance speaking skills in fourth-grade students at SDN 5 Wawolesea.